2021
DOI: 10.3390/brainsci11091140
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Binding Processes of Working Memory and Vascular Risk Profile in Adults

Abstract: Episodic buffer (EB), a key component of working memory, seems to have a rather complicated function as part of binding processes. Recent papers on the field claim that binding processes of working memory (WM) are assisted by attention and executive functions. On the same page, vascular pathology is gaining more ground as the main underlying cause for many brain pathologies. Hypercholesterolemia, hypertension, obesity, diabetes, lack of exercise and smoking are the most common risk factors that people of all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…The examination of feature binding in aging is also pertinent for clinical reasons. Indeed, feature binding of WM representations has been proposed as a marker for AD (Parra et al, 2010 , 2011 ; Cecchini et al, 2022 for a review) and for individuals at vascular risk (Bika et al, 2021 ). Research has found individuals with AD, and asymptomatic carriers, to indicate decreased hippocampal volume associated with object-to-location binding impairments (Liang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The examination of feature binding in aging is also pertinent for clinical reasons. Indeed, feature binding of WM representations has been proposed as a marker for AD (Parra et al, 2010 , 2011 ; Cecchini et al, 2022 for a review) and for individuals at vascular risk (Bika et al, 2021 ). Research has found individuals with AD, and asymptomatic carriers, to indicate decreased hippocampal volume associated with object-to-location binding impairments (Liang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [ 28 , 45 ] have argued that working memory is an important predictor of progression from MCI to AD dementia. Regarding impaired working memory in vascular aging, its correlation with vascular risk factors has been explored [ 46 ]; adults bearing vascular risk factors had significantly lower performance on binding functions of working memory. The basis of the correlation is given through pathologic changes to the macro- and microvasculature, which could disrupt blood vessel integrity, secondarily causing neuronal injury, structural and functional brain damage.…”
Section: Introductionmentioning
confidence: 99%